MORAL VALUES IN WAYANG WAHYU LAKON NAAMAN SANG SENOPATI FOR CHARACTER EDUCATION - Seruni Widaningrum (Jurnal Pendidikan Karakter, 2023)
This research aims to analyze the moral values contained in Wayang wahyu performances. Wayang wahyu grows and develops among Catholics as a proclamation of church teachings. Church teachings have moral values that need to be instilled in humans for character education. Dalang presents a reflection of a life that is full of moral messages through the drama of the wayang Wahyu so that the delivery of moral messages becomes familiar to the Javanese community. With the presence of Wayang wahyu, it is expected that the audience can capture moral messages useful for reflecting on the lives of Catholics. This study aims to reveal the moral values contained in lakon Naaman Sang Senopati. This research uses a qualitative descriptive method with a value analysis approach. The results of this study can be concluded that the Wayang Wahyu performance is an effort by Catholics to bring their teachings closer to the Javanese community. The performance of Naaman Sang Senopati contains moral values that are useful for building the character of Catholics. The result of this study is that this performance is full of values of religiosity, trust, self-surrender, nationalism, obedience, universality, and love.